2004
DOI: 10.1590/s0034-72992004000500013
|View full text |Cite
|
Sign up to set email alerts
|

Efeito da mitomicina C em cultura de estroma de pólipos nasais eosinofílicos: indução de apoptose em eosinófilos

Abstract: A polipose nasossinusal eosinofílica é uma afecção comum a várias doenças, determina acometimento extenso dos seios paranasais e possui grande tendência à recidiva após tratamento. Os eosinófilos exercem papel essencial na patogênese, relacionada a baixo índice de apoptose e a longa permanência destas células ativas nos tecidos. OBJETIVO: Este estudo teve por objetivo avaliar o efeito da mitomicina C na indução de apoptose em eosinófilos presentes no estroma de pólipos nasais eosinofílicos. FORMA DE ESTUDO: Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Crossara et al Showed that MMC is efficient in inducing eosinophil apoptosis when these are present in the stroma of eosinophylic nasal polyps. A paired study with nine cultivated samples was carried out and we observed that the MMC treated cultures presented 12-hour apoptosis rate significantly higher in relation to the control group (p<0.001) 15 . MMC proved to have inhibitory action on DNA synthesis, inhibiting the proliferation of many cell lines.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Crossara et al Showed that MMC is efficient in inducing eosinophil apoptosis when these are present in the stroma of eosinophylic nasal polyps. A paired study with nine cultivated samples was carried out and we observed that the MMC treated cultures presented 12-hour apoptosis rate significantly higher in relation to the control group (p<0.001) 15 . MMC proved to have inhibitory action on DNA synthesis, inhibiting the proliferation of many cell lines.…”
Section: Discussionmentioning
confidence: 90%
“…This cytokine increase is related to the genetic aspect of the NSP eosinophilic cells 5 . Most of the treatment available is based on the use of systemic steroids for a short duration and topical steroid for a longer period, besides surgery 15 . MMC is an antineoplastic agent produced by the Streptomyces caespitosus that has been used as antiproliferative agent in the 0.4mg/ml concentration.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the treatment available is based on the use of systemic steroids for a short duration and topical steroid for a longer period, besides surgery 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Paired studies with nine cultivated samples were carried out. The polyps were treated with 0.4mg/ml for five minutes and were dyed with hematoxylin eosine 15 .…”
Section: Introductionmentioning
confidence: 99%